The Influence of Leadership and Interpersonal Communication on the Performance of Lecturers of Tribuana University Kalabahi, Alor-NTT District - Nehemia Fanpada (Peneliti.net, 2020)
Perfomanced is the work result who has achieved by someone in doing the task in a institution. In achieve the good perfomanced, it need supported by good leadership and communication. The research aimed to see how the leadership and interpersonal communication has effected in to increase lecturer performance of Tribuana Kalabahi University. The population of this research were all the lecurers as many as 40 person. The data was empiris data which gained from questionnaire which has been tested the validity and reliability. Data that collected has been analyzed by descriptive analysis, and then hypothesis used path analysis. The result research shown that there is directly affect towards perfomanced. Interpersonal communication has directly affected towards interpersonal communication. Implication of the research are to increasing the leadership and good interpersonal communication in the achievement of good perfomanced